On-farm pre-weaning growth performance of Washera, Farta and their crossbred lambs in selected districts of western Amhara Region, Ethiopia - Adimasu, Esubalew; Alemayehu, Kefyalew; Getachew, Tesfaye (Ethiopian Journal of Science and Technology, 2025)
The objective of the study was to evaluate the pre-weaning growth performance of Farta, Washera, and their cross-sheep lambs. The study was conducted in Farta and Lay Gayint districts of the Amhara National Regional State. The data were collected from November 2016 to May 2017. A total of 132 sheep, i.e., 82 Farta, 20 Washera, and 30 Washera-Farta crossbred, were selected using purposive sampling technique to assess their pre-weaning growth performance. Growth data was analyzed using SAS Version 9.1.3. (SAS, 2008). Mean birth weight (± SE in kg) was 2.7±0.30 for Farta, 3.1±0.14 for Washera, and 2.9±0.08 for Washera-Farta crossbred lambs. Weaning weights were 10.9±0.30 kg for Farta, 13.1±0.50 kg for Washera, and 12.2±1.1 kg for Washera-Farta crossbreds. Daily weight gain calculated from birth to 30 days was 89.4±6.44 g for Farta, 119.4±23.53 g for Washera and 111.4±10.46 g for Washera-Farta crossbreds. Weight gain from birth to 90 days was 88.8±3.21 g, 103.2±11.75 g, and 111.9±5.22 g, respectively. Washera breed was significantly heavier at birth and at weaning age, followed by crossbred lambs. Crossbred lambs were not significantly bigger than Farta lambs. This means crossing the two breeds did not have advantage and selection breeding of Farta sheep by itself will be adequate.